Bilateral ovarian yolk sac tumor in adolescent - Yisel González Ríos; Leidelén Esquivel Sosa; Yurisandra Jiménez González (Centro Provincial de Información de Ciencias Médicas, 2023)
The case report of a 15-years-old adolescent is presented, who was assisted at José Luis Miranda University Pediatric Provincial Hospital from Villa Clara, referred from her health area due to an intense pelvic pain for 3 days, nausea and fever of 38.5 °C. After carrying out the clinical exam and the pertinent laboratory tests, it was decided to practice the complete tumor resection. During the procedure a sample for histologic study was taken that confirmed the existence of an ovarian yolk sac tumor, reason why she was operated again to extirpate the contralateral ovary and the infiltrated omentum. Later on polychemotherapy was indicated according to the protocol and the post-treatment clinical course was satisfactory.